5 Therapy for asthma and COPD. (1st December 2018) - Barnes, Peter J
Abstract: A hundred years ago the main treatments for obstructive lung disease were adrenal gland extracts, herbally-derived sympathomimetic ephedrine and anticholinergics, such as atropine. There have been extraordinary advancers in the pharmacological therapy of asthma and COPD, yet the major classes of therapy we use today are based on these original therapies – long-acting β2 -agonists (LABA) derived from adrenaline and muscarinic receptor antagonists (LAMA) and inhaled corticosteroids (ICS) developed from the adrenal cortex hormone cortisol. Triple fixed-dose inhalers containing all 3 drugs have now been developed and are convenient for some patients. In asthma, by far the greatest advance has been the Introduction of ICS for control of the underlying eosinophilic inflammation of the airways. Although ICS are effective in most patients, there is often very poor adherence as symptoms are intermittent. In a new strategy, instead of a short-acting β2 -agonist, such as salbutamol, patients use a reliever inhaler containing a rapidly-acting LABA formoterol combined with an ICS. This provides much better control of asthma and is a simple strategy for most patients. At the other end of the spectrum, patients with eosinophilic severe asthma not controlled on conventional therapies may now be controlled with biologics, which include antibodies against immunoglobulin-E, interleukin-5 and interleukin-4 receptor. In COPD the mainstay of treatment is LABA and LAMA, often as a combination inhaler, whereas ICS are only effective in a proportion of patients that also have eosinophilic inflammation. New safe anti-inflammatory treatments are needed to prevent the progression and exacerbations of COPD.